METALS AND ELECTROCHEMICAL CORROSION (American Journal of Technology and Applied Sciences, 2025)
Metals are widely used in many fields due to their physicochemical properties and industrial importance. However, the long-term use and stability of metals are faced with problems associated with electrochemical corrosion. In this article, we will discuss the electrochemical corrosion processes of metals, their causes and methods of prevention.